Assessing the genotoxic potential of freshwater sediments after extensive rain events – Lessons learned from a case study in an effluent-dominated river in Germany. (1st February 2022) - Shuliakevich, Aliaksandra; Muz, Melis; Oehlmann, Jörg; Nagengast, Laura; Schröder, Katja; Wolf, Yvonne; Brückner, Ira; Massei, Riccardo; Brack, Werner; Hollert, Henner; Schiwy, Sabrina
Highlights: Presence of the genotoxic potential in all freshwater sediment samples. Strong increase of genotoxicity after extensive rain events and release of the rainwater overflow basin. PAHs, nitroarenes, aromatic amines, and polycyclic heteroarenes were identified as possible genotoxicity drivers. Abstract: Wastewater treatment plant effluents and releases from rainwater overflow basins can contribute to the input of genotoxic micropollutants in aquatic ecosystems. Predominantly lipophilic genotoxic compounds tend to sorb to particulate matter, making sediment a source and a sink of pollution. Therefore, the present study aims to investigate the genotoxic potential of freshwater sediments (i) during the dry period and (ii) after extensive rain events by collecting sediment samples in one small anthropogenically impacted river in Germany up- and downstream of the local wastewater treatment plant. The Micronucleus and Ames fluctuation assays with Salmonella typhimurium strains TA98, TA100, YG1041, and YG1042 were used to assess the genotoxic potential of organic sediment extracts. For evaluation of possible genotoxicity drivers, target analysis for 168 chemical compounds was performed. No clastogenic effects were observed, while the genotoxic potential was observed at all sampling sites primarily driven by polycyclic aromatic hydrocarbons, nitroarenes, aromatic amines, and polycyclic heteroarenes. Freshwater sediments' genotoxic potential increased after extensive rain events due to sediment perturbation and the rainwater overflow basin release. In the present study, the rainwater overflow basin was a significant source for particle-bound pollutants from untreated wastewater, suggesting its role as a possible source of genotoxic potential. The present study showed high sensitivity and applicability of the bacterial Salmonella typhimurium strains YG1041 and YG1042 to organic sediment extracts to assess the different classes of genotoxic compounds. A combination of effect-based methods and a chemical analysis was shown as a suitable tool for a genotoxic assessment of freshwater sediments. Graphical abstract: Image, graphical abstract